Tindak Tutur dalam Studi Kasus Pakeliran Wayang Kulit Purwa Sukron Suwondo (Kajian Sosiopragmatik) - Harbono Harbono (Journal on Education, 2023)
This research is descriptive qualitative with a holistic critical approach, by examining three factors, namely: (1) objective factors are three stories that focus on the types of speech acts found, dominant speech acts, direct/indirect speech strategies, implicature and pragmatic power and the unique features of pakeliran which include elements of working on chess, working on musical instruments, working on sabet, and working on sanggit plays; (2) the genetic factor is conducting in-depth interviews on the reasons for Sukron Suwondo as the unconventional mastermind in playing three stories about the findings of objective factors; (3) the affective factors of public perception, namely the puppeteers, humanists, art experts, lovers of the art of puppetry, regarding the findings on the objective factors of working on Pakekiran Sukron Suwondo, it will be known the positive and negative impacts on Pakekiran. The findings of the research results are as follows. First, the Sukron Suwondo shadow puppet show underwent a change in form, elements of work on, and meaning. Second At this time, Sukron Suwondo appears as a puppeteer who is different from other puppeteers, with all his strengths and weaknesses, even by some people he is considered a puppeteer who is controversial and unconventional. The third of the three speech act stories is the dominant play (TTKUMDSLSMG), namely there are 5,085 speech acts. The four speech strategies that choose to use indirect types of speech acts are used more often than direct speech acts. The implication of compliance with the maxims of the principle of cooperation is needed when speakers and speech partners emphasize the element of cooperation in speech acts, therefore other communication principles are needed, namely the principle of politeness (PSS), the principle of relevance (PR), the principle of humor ( PH), and the principle of harmony (PK).